Socialization of Interest in Literacy and Numeracy at SMP Negeri 2 Bangorejo: Sosialisasi Minat Literasi Dan Numerasi Pada SMP Negeri 2 Bangorejo - Dimas Priyagung Banar; Barep Yohanes; Dzurotul Mutimmah (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2024)
This article is the result of activities to socialize interest in literacy and numeracy for students at SMP Negeri 2 Bangorejo. The socialization was carried out to solve the problems faced regarding the plan to implement the Independent Curriculum at the junior high school level. The transition or trial transition period causes confusion among schools regarding the activities that must be carried out and examples of activities that support the program, such as literacy and numeracy activities. Discussion and assessment of the Independent Curriculum program was carried out by looking at the Teaching Campus program which had been carried out by students and the Ministry of Research, Technology and Higher Education. The experience of being a Field Assistant Lecturer in the Teaching Campus program is the basis for activities carried out to improve the literacy and numeracy skills of partner schools’ students. The results obtained from this sociali-zation activity show that the interest in literacy and numeracy of SMP Negeri 2 Bangorejo students looks good and positive. Students are more interested in learning literacy and numeracy through activities that are directly related to daily life.